Development and psychometric assessment of a novel survey to measure care coordination from the specialist's perspective. (2nd April 2019) - Vimalananda, Varsha G.; Fincke, Benjamin Graeme; Qian, Shirley; Waring, Molly E.; Seibert, Ryan G.; Meterko, Mark
Abstract : Objective: To develop an online survey of care coordination with primary care providers as experienced by medical specialists, evaluate its psychometric properties, and test its construct validity. Data Sources: Physicians (N = 633) from 13 medical specialties across the Veterans Health Administration. Study Design: We developed the survey based on prior work (literature review, specialist interviews) and by adapting existing measures and developing new items. Multitrait scaling analysis and confirmatory factor analysis were used to assess scale structure. We used multiple linear regression to examine the relationship of the final coordination scales to specialists' overall experience of care coordination. Data Collection: November 2016‐December 2016. Principal Findings: Results suggest a 13‐item, four‐factor survey [Relationships ( k = 4), Roles and Responsibilities ( k = 4), Communication ( k = 3), and Data Transfer ( k = 2)] that measures the medical specialist experience of coordination with good internal consistency reliability, convergent validity, discriminant validity, and goodness of fit. Together, the four scales explained nearly 50 percent of the variance in specialists' overall experience of care coordination. Conclusions: The 13‐item Coordination of Specialty Care—Specialist Survey (CSC‐Specialist) is the first of its kind. It can be used alone or embedded in other surveys to measure four domains of care coordination as experienced by medical specialists.